STUDI RENDEMEN DAN KUALITA MOULDING BEBERAPA JENIS KAYU INDUSTRI INDONESIA (Study of moulding recovery and quality of several indonesia industrial woods) - Bakir Ginoga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
The study describes moulding recovery and quality of seven Indonesian industrial wood species, i,e. meranti putih (shorea koordersii), sungkai (phenomena canescens jack). Cempaka (elmerillia ovalis dandy), dahu (dracontomelon dao), perupuk (solenospermum sp.) meranti merah (shorea sp.). and kapur (dryobalanops sp.).It is found that volume recovery varies from 38.7 to 80.2 per cent. An optimal allowances for moulding raw material are 3.0 mm in thickness and 9.6 mm in yidthSungkai, dahu, perupuk and kapur species produced the best moulding quality. Moulding quality of the other species is found to be of good quality.The processing of cempaka and meranti species, especially on their radial surface or quarter swan timber, should be undertaken carefully because of they have genetical interlocked grains.